The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2337/dc13-1198
|View full text |Cite
|
Sign up to set email alerts
|

Total and Cause-Specific Mortality by Elevated Transferrin Saturation and Hemochromatosis Genotype in Individuals With Diabetes: Two General Population Studies

Abstract: OBJECTIVEMortality is increased in patients with hereditary hemochromatosis, in individuals from the general population with increased transferrin saturation (TS), and also in patients with type 1 diabetes and increased TS from a highly specialized diabetes clinic. Thus, we have recommended targeted screening for TS in specialized diabetes clinics. Whether mortality is also increased in individuals from the general population with diabetes and increased TS is unknown. RESEARCH DESIGN AND METHODSIn two Danish p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…Our results are in accordance with previous evidence that increased transferrin saturation is associated dose-dependently with increased total mortality (23)(24)(25). Another population-based study examined risk of premature death in individuals of mixed ethnicity with serum ferritin Ն200 vs 50 -99 g/L and did not find any association (9 ); however, compared to the present study, that study was smaller (n ϭ 1604), had shorter follow-up (12 years), and had actual HRs for total mortality of 0.7 (0.4 -1.3) and 0.9 (0.4 -2.1) in white women and men, respectively, overlapping with the present HRs.…”
Section: Ferritin and Mortalitysupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in accordance with previous evidence that increased transferrin saturation is associated dose-dependently with increased total mortality (23)(24)(25). Another population-based study examined risk of premature death in individuals of mixed ethnicity with serum ferritin Ն200 vs 50 -99 g/L and did not find any association (9 ); however, compared to the present study, that study was smaller (n ϭ 1604), had shorter follow-up (12 years), and had actual HRs for total mortality of 0.7 (0.4 -1.3) and 0.9 (0.4 -2.1) in white women and men, respectively, overlapping with the present HRs.…”
Section: Ferritin and Mortalitysupporting
confidence: 83%
“…Finally, iron supplementation has also been associated with risk of premature death (26 ). The association of increased plasma ferritin with increased risk of cancer and endocrinological mortality is in accordance with previous studies of increased transferrin saturation and cause-specific mortality (24,25 ). The association of increased plasma ferritin with increased risk of cardiovascular mortality is in accordance with a previous study of heterozygosity for hereditary hemochromatosis; however, the finding is contradictory to a previous metaanalysis of ferritin concentrations with coronary heart disease, although that metaanalysis did not cover other cardiovascular diseases or mortality (27 ) and was primarily based on small study populations with shorter follow-up than our study.…”
Section: Ferritin and Mortalitysupporting
confidence: 75%
“…Increased transferrin saturation showed a dose-dependent association with an increased total mortality (65). A moderate to marked increase of ferritin concentrations also predicted early death in a dose-dependent linear manner among the general population (65) and among patients with T2D (66). Clinicians must be aware of the importance of preventing, diagnosing in a timely manner, and treating disturbances of iron metabolism in patients with MetS and T2D.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…In a 1991 study of Canadian patients with hemochromatosis, diabetes did not increase the risk of death after data were controlled for the presence of cirrhosis [140]. In a large study of Danes reported in 2014, the mortality risk in individuals with diabetes was more than threefold greater in those with HFE p.C282Y/p.C282Y than in those with HFE wt/wt genotypes [141]. …”
Section: Complications Of Diabetesmentioning
confidence: 99%